2015
DOI: 10.1038/jcbfm.2015.117
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic Acid Inhibition by HET0016 Offers Neuroprotection, Decreases Edema, and Increases Cortical Cerebral Blood Flow in a Pediatric Asphyxial Cardiac Arrest Model in Rats

Abstract: Vasoconstrictive and vasodilatory eicosanoids generated after cardiac arrest (CA) may contribute to cerebral vasomotor disturbances and neurodegeneration. We evaluated the balance of vasodilator/vasoconstrictor eicosanoids produced by cytochrome P450 (CYP) metabolism, and determined their role on cortical perfusion, functional outcome, and neurodegeneration after pediatric asphyxial CA. Cardiac arrest of 9 and 12 minutes was induced in 16- to 18-day-old rats. At 5 and 120 minutes after CA, we quantified the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…We also observed that there was a larger decrease in Cyt-ox in the brain compared to muscle during untreated VF, which may represent higher concentrations of Cyt-ox in the brain 35 or the brain's vulnerability to hypoxia.…”
Section: Comparison Of the Brain Vs Muscle Hemodynamics And Metabolismmentioning
confidence: 56%
See 1 more Smart Citation
“…We also observed that there was a larger decrease in Cyt-ox in the brain compared to muscle during untreated VF, which may represent higher concentrations of Cyt-ox in the brain 35 or the brain's vulnerability to hypoxia.…”
Section: Comparison Of the Brain Vs Muscle Hemodynamics And Metabolismmentioning
confidence: 56%
“…Interestingly, we also observed an increase in cerebral total Hb of ~200 s after VF induction (which was not observed in the muscle); this is consistent with a previous study by Shaik et al who showed increased vasodilator eicosanoids in the cerebral cortex during CA in rats. 35 Increased cerebral total Hb only in the cerebral tissue during untreated VF may represent the cerebral autoregulation through cerebral vasodilation.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Previous studies have not been able to identify the exact time and magnitude of the hyperemic peak and stabilized hypoperfusion post-ROSC due to the relatively poor temporal resolution (~5-30min) [7,10,23]. Interestingly, in a pediatric model of asphyxial CA, Manole et al [9] and Shaik et al [24] both did not observe a hyperemic peak in cortical CBF using MRI and LSI, respectively. Their results suggest that post-ROSC cerebral hemodynamics vary between adults and children.…”
Section: Discussionmentioning
confidence: 97%
“…CSD has recently been reported to be associated with an increase in 20-HETE synthesis and reduced CBF in rat model. Administration of 20-HETE inhibitor ameliorated the reduction in CBF, decreased edema and afforded neuroprotection (282, 283). …”
Section: 20-hete In Stroke and Traumatic Brain Injurymentioning
confidence: 99%